Carta de Roberto H. Todd a Francisco González Carmona - Todd, Roberto H.; González Carmona, Francisco (My University, 1935)
Adquisición de una casa para la viuda e hijos de Manuel Ángel Martínez Dávila.
Keywords: Martínez Dávila, Manuel A.,1883-1934; Porrata Doria, Adolfo